Does Japan Still Matter? Past Tendencies and Future Opportunities in the Study of Japanese Firms. (28th May 2014) - Endo, Takahiro; Delbridge, Rick; Morris, Jonathan
<x xml:space="preserve">Abstract</x> This paper engages with the question 'does Japan still matter' by systematically reviewing publication patterns in peer‐reviewed academic journal articles addressing Japanese firms and their management practices, illustrating the academic discourse surrounding Japanese firms over four decades, and by identifying future research opportunities. Initially, particularly from the 1980s when Japanese firms came to prominence, these practices tended to be identified as 'best practice'. However, at least in part due to socio‐economic changes, this tendency has become less prominent since the 'bubble economy' burst. Instead, three broader developments are observed: the examination of the continuity and change in the traditional Japanese model, a more complex approach that involves multiple themes of research, and leveraging new contexts to examine Japanese firms, including the long‐term recession, the rise of the East Asian economy, and the increasing importance of corporate social responsibility.